Reciprocity vs. Commitment in Bank Marketing Strategies - Silva, Sergio Da; Santo, Barbara Espirito; Sigrist, Felipe; Matsushita, Raul (International Journal of Business, Economics and Management, 2022)
The purpose of this paper is to evaluate how bank marketing should respond to the banker’s paradox. Customers who need money the most are at risk for credit and thus unable to obtain a loan, according to the banker’s paradox. This relates to the fact that the client-bank relationship is based on reciprocity rather than commitment. We hypothesize that a bank marketing strategy that masquerades as a commitment will be more successful because clients have evolved to understand the superiority of commitment and be receptive to its cues. We put this marketing strategy to the test by sending 413 participants advertising slogans based on two types of cooperation: reciprocity and commitment. Our findings indicate that people do prefer bank slogans that imply a commitment-based relationship. The work’s novelty comes from its contribution to the literature of an evolutionary psychology perspective, which shows that commitment is a critical component of a successful bank marketing strategy.